Multifunctional tribometer development and performance study of CuCrZr-316L material pair for ITER application. (December 2017) - Chen, Z.; Hillairet, J.; Turq, V.; Song, Y.; Yang, Q.; Lombard, G.; Vulliez, K.; Mollard, P.; Volpe, R.; Bernard, J.M.; Hernandez, C.; Ferlay, F.; et al.
Abstract: Radio-Frequency (RF) contacts are key components on the International Thermonuclear Experimental Reactor (ITER) Ion Cyclotron Resonance Heating (ICRH) antenna, and these components are facing big challenges such as 2 kA operation current load and intensive sliding under up to 250 °C in high vacuum. Stainless steel (SS) 316L and CuCrZr are most likely to be applied as base materials for the conductor and the RF contacts louvers. To evaluate the performance of the selected materials, their electrical and tribological behaviors have to be studied. A multifunctional tribometer which can mimic the ITER ICRH RF contacts' relevant working conditions was designed and built in CEA. The contact resistance (Rc) and coefficient of friction (CoF) of CuCrZr-316L pair were researched on this tribometer. Highlights: A tribometer that can mimic ITER ICRH RF contact working conditions was developed. The coefficient of friction and contact resistance can be measured simultaneously. The load plates that supply the normal contact force can be adjusted without opening the vacuum vessel. The performance of CuCrZr/316L material pair was evaluated for ITER RF contact application.